Pengembangan LKPD IPA Menggunakan Model Problem Based Learning pada Materi Sifat-Sifat Cahaya untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas V Sekolah Dasar - Hariyati, Agung; Widi Winarni, Endang; Muktadir, Abdul (UNIB Press, 2025)
Problem based learning model is one of the learning models that can be used in the classroom learning process that aims to improve students' critical thinking skills. The purpose of writing this paper is to describe the Science Student Worksheet, the concept and principles of problem based learning on the dimensions of the ability to provide simple explanations, induce induction results, and define terms in science learning on the Properties of Light for fifth grade elementary school students. The research method is research and development (research and development) of the ADDIE model. The subjects of this study consisted of two classes in two schools. Class V of SDN Sukaraja is the subject for the limited trial and class V of SDN Rantau Telang is the subject for the effectiveness test. Data were collected through observation, interviews, questionnaires, and test results. Data were processed using percentages and ranges of values classically and individually. The results of this study indicate that the implementation of the problem based learning model has proven effective in improving the critical thinking skills of fifth grade students of SDN Rantau Telang because it obtained a value of 0.7248 and is included in the high category. The recommendation from this study is that every teacher can use a good learning model and can actively involve students in learning activities in order to improve critical thinking skills and improve learning outcomes.